#TITLE_ALTERNATIVE# - HENDRIANA , DEDEN
In this paper, we study the necessary condition for the boundedness of fractional integral operators on the Morrey spaces. If these results are combined with previous research then it is obtained the necessary and sucient condition for the boundedness of fractional integral operators on the Morrey spaces. The necessary condition is obtained through the use of characteristic function as one member of the Morrey space and value of fractional integral operators on an open balls. Especially, the necessary condition for the boundedness of generalized fractional integral operators on the generalized Morrey spaces. The condition that is satised for the necessary condition are doubling condition on fractional integral operators and the generalized Morrey spaces.